The burning room : a novel - Connelly, Michael; Copyright Paperback Collection (Library of Congress) (New York, NY : Vision, 2014)
"In the LAPD's Open-Unsolved Unit, not many murder victims die a decade after the crime. So when a man succumbs to complications from being shot by a stray bullet ten years earlier, Bosch catches a case in which the body is still fresh, but any other clues are virtually nonexistent. Now Bosch and his new partner, Detective Lucia Soto, are tasked with solving a murder that turns out to be highly charged and politically sensitive. Beginning with the bullet that has been lodged for years in the victim's spine, they must pull new leads from years-old evidence, and these soon reveal that the shooting was anything but random. When their work starts to threaten careers and lives, Bosch and Soto must decide whether it's worth risking everything to find the truth, or if it's safer to let some secrets stay buried."--Page [4] cover.
Includes excerpt from The Crossing.
Keywords: Cold cases (Criminal investigation) -- Fiction; Murder -- Investigation -- Fiction; Police -- Los Angeles -- Los Angeles -- Fiction; Los Angeles (Calif.) -- Fiction; Cold cases (Criminal investigation) -- Fiction; Murder -- Investigation -- Fiction; Police -- Los Angeles -- Los Angeles -- Fiction; Los Angeles (Calif) -- Fiction; Mystery fiction